Upaya Peningkatan Hasil Belajar Lompat Tinggi Gaya Straddle Dengan Menggunakan Modifikasi Lompat Tali Pada Siswa Siswi Kelas VI SD - Ginting, Elvita Ersama Br; Bangun, Sabaruddin Yunis; Siregar, Samsuddin (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This research aims to determine the improvement in the learning outcomes of the straddle high jump style among sixth-grade students of SD Negeri 040515 Tiga Jumpa, Kec. Barus Jahe, Kab. Karo by using modified rope jumping. This study uses the classroom action research (CAR) method. The sample in this study consists of all the sixth-grade students of SD Negeri 040515 Tiga Jumpa, Kec. Barus Jahe, Kab. Karo, with a total of 30 students divided into 18 boys and 12 girls. Out of 30 students, 14 (46.67%) have reached the level of learning mastery. Meanwhile, 16 students (53.33%) have not yet reached the level of learning completeness. With an average student learning outcome score of 69.79. Meanwhile, in Cycle II, it can be seen that the students' ability to complete the learning outcome test in a classical manner has improved. Out of 30 students, 26 (86.67%) have achieved the level of learning mastery, while 4 (13.33%) have not yet reached the level of learning mastery. With an average student learning outcome score of 77.36, it indicates an improvement from the previous results. Conclusion, that by using modified rope jumping, it can improve the learning outcomes of the straddle high jump style among sixth-grade students of SD Negeri 040515 Tiga Jumpa, Kec. Barus Jahe, Kab. Karo. Keywords: Sports, Athletics, High Jump